Hydro-geomorphologic GIS database in Northern Portugal, between 1865 and 2010: Temporal and spatial analysis - Santos, Monica (2014)
Floods and landslides are the natural hazards that most affect Northern Portugal. This paper presents the DISASTER database results for Northern Portugal, containing occurrences of floods and landslides between 1865 and 2010. The research carried out was based on press articles published in national and regional newspapers, but focusing exclusively the occurrences that caused personal damage, including deaths, injured, missing, evacuees and displaced people, regardless of the number of people affected and the economic value of damages. A total of 613 occurrences were recorded, which 18% are landslides and 82% are floods. These occurrences were responsible for 198 deaths, 58 injured, 34 disappeared, 1804 evacuated and 15,918 displaced. The trend analysis shows an increase of 0.17 occurrences/decade. The obtained results show the occurrences concentration in the more urbanized areas and along larger rivers.